An efficient Agrobacterium-mediated transient transformation system and its application in gene function elucidation in Paeonia lactiflora Pall - Guan, Shixin; Kang, Xuening; Ge, Jiayuan; Fei, Riwen; Duan, Siyang; Sun, Xiaomei (Frontiers in Plant Science, 2022)
Paeonia lactiflora Pall. is known as the king of herbaceous flowers with high ornamental and precious medicinal value. However, the lack of a stable genetic transformation system has greatly affected the research of gene function in P. lactiflora. The Agrobacterium-mediated transient gene expression is a powerful tool for the characterization of gene function in plants. In this study, the seedlings of P. lactiflora were used as the transformation receptor materials, and the efficient transient transformation system with a GUS reporter gene was successfully established by Agrobacterium harboring pCAMBIA1301. To optimize the system, we investigated the effects of germination time, Agrobacterium cell density, infection time, acetosyringone (AS) concentration, co-culture time, negative pressure intensity, Tween-20 concentration and different receptor materials on the transient transformation efficiency of P. lactiflora. The results showed that the highest transient transformation efficiency (93.3%) could be obtained when seedlings in 2-3 cm bud length were subjected to 12 h infection of resuspension solution comprising 1.2 OD600 Agrobacterium, 200 μM AS and 0.01% Tween-20 under 10 of negative pressure intensity followed by 3 days of co-culture in darkness condition. This method is more suitable for the study of gene function in P. lactiflora. Subsequently, stress resistance genes PlGPAT, PlDHN2 and PlHD-Zip were used to verify the effectiveness of this transformation system. These results can provide critical information for identification of key genes in non-model plants, such as P. lactiflora, and promote the development of molecular biology research for P. lactiflora.